Effect of temperature on corrosion behavior of dissimilar weldments of Inconel 718 vs ASS 316 with mixer of sodium sulfate and vanadium pentoxide deposit - K. Balaji, Mr.; K. Brahma Raju, Dr.; K. Venkata Subbaiah, Dr. (International Journal of Engineering and Technology, 2018)
The effect of temperature on corrosion behavior of dissimilar weldments of Inconel 718 Vs ASS 316 was investigated in the presence of sodium sulfate (Na2SO4) and vanadium pentoxide (V2O5) salt mixer at 950oC, 10500C and 11500C for 1hr heating followed by 20min cooling in the room temperature. The results indicated that the initial sodium sulfate (Na2SO4) and vanadium pentoxide (V2O5) salt coating caused acceleration in oxidation, resulting in the formation of scales developed by the reduction in oxidation rate due to the evaluate of CO/CO2 gas. The weight change of parent metal and weldment were recorded as the temperature. The morphologies of deposits were also analyzed, using SEM.Â